Evaluasi Kesesuaian Lahan Permukiman Perum Bakti Persada Indah Kelurahan Purwoyoso Semarang (Studi Kasus Kesesuaian Lahan....) - Sutrisno Anggoro, Imam Buchori (Program Studi Ilmu Lingkungan Program Pasca Sarjana UNDIP), Hartono (Teknis, 2015)
Land use is primarily residential zone uninhabitable, land units that have a large slope soil layer with low carrying capacity of the soil and rock that is not stable, less vegetative is an area that is prone to landslides. The land use changes and continuously can lead to the use of space be not as intended, many catastrophic events that arise due to changes in land use. Settlements built around the hills are generally less concerned about the stability of the slope, and the structure of rocks, from the geological processes that occur in the area and did not realize the potential danger of landslides that any time would threaten life and property. As with settlement Bakti Persada Indah Housing construction in Semarang Ngaliyan hill temple in Industrial Area. Based on this, it felt quite relevant location for research. This study uses a case study approach as well as on settlement construction in the residential hills of BPI in Block Q village location Purwoyoso Ngaliyan District of Semarang, in his review of the impact of land suitability can cause vulnerability to landslides. From the analysis of land suitability can be stated that the residential hill area BPI Village location Purwoyoso Ngaliyan District of Semarang to residential areas with a low density of the suitability of land is still appropriate.Keywords: evaluation, land suitability, settlements.